2014
DOI: 10.1007/s10916-014-0181-3
|View full text |Cite
|
Sign up to set email alerts
|

Privacy and Security in Mobile Health Apps: A Review and Recommendations

Abstract: In a world where the industry of mobile applications is continuously expanding and new health care apps and devices are created every day, it is important to take special care of the collection and treatment of users' personal health information. However, the appropriate methods to do this are not usually taken into account by apps designers and insecure applications are released. This paper presents a study of security and privacy in mHealth, focusing on three parts: a study of the existing laws regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
150
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(157 citation statements)
references
References 31 publications
3
150
0
4
Order By: Relevance
“…8 Despite the enthusiasm for digital health there are pitfalls and several studies have demonstrated the potential for certain apps to cause patient harm. [9][10][11] Furthermore, the use of mobile devices in the clinical arena poses specific security and privacy challenges 12 that must be addressed in order to mitigate the risks of inadvertently breaching highly sensitive and confidential patient-identifiable data.…”
Section: Introductionmentioning
confidence: 99%
“…8 Despite the enthusiasm for digital health there are pitfalls and several studies have demonstrated the potential for certain apps to cause patient harm. [9][10][11] Furthermore, the use of mobile devices in the clinical arena poses specific security and privacy challenges 12 that must be addressed in order to mitigate the risks of inadvertently breaching highly sensitive and confidential patient-identifiable data.…”
Section: Introductionmentioning
confidence: 99%
“…Martinez-Pérez et al [63]. reviewed the standards and certifications about security and privacy in North America and the European countries.…”
Section: Privacy and Security Of Mobile Appsmentioning
confidence: 99%
“…They state that 'In practice, these laws are too open and too old, and need to be revised and reformulated taking into account the current technologies, industries and healthcare fields, focusing especially on mHealth and the mobile apps industry, which is continuously expanding.' [63] Mamlin et al [64]. also point out that the laws, in the United States, need to be updated to match the current methods for recording and transmitting data [64].…”
Section: Privacy and Security Of Mobile Appsmentioning
confidence: 99%
“…Martínez et al, (9) presentó algunos requisitos legales que permiten mantener la seguridad y privacidad de la información y que se encuentran organizados en las siguientes categorías: cobertura de la información de los pacientes, requerimientos y métodos utilizados para recoger la información, requisitos de consentimiento, retención de datos, seguridad durante la adquisición, transmisión y almacenamiento de los datos y obligaciones de notificación. Arora et al, (10) analizaron los factores de riesgo en la salud móvil y plantearon posibles soluciones para mitigarlos durante los procesos de identificación, autenticación, trasmisión de la información y control de acceso.…”
Section: Introductionunclassified